PENGARUH MODEL PEMBELAJARAN PROJECT-BASED LEARNING BERBASIS TPACK DALAM IMPLEMENTASI KURIKULM MERDEKA TERHADAP HASIL BELAJAR BIOLOGI DAN KEMAMPUAN BERPIKIR KREATIF SISWA KELAS X - Sil, Sil Hidayatullah (Cocos Bio, 2024)
This research aimed to determine the impact of the TPACK based on Project Based Learning model on biology learning outcomes and the creative thinking skills of tenth-grade students. This study was used experimental research conducted with a quantitative approach. The research employed a Quasi-Experimental design with a nonequivalent control group, comprising experimental and control groups. The research population included all tenth-grade students (phase E) of SMAN 1 LENEK for the 2024/2025 academic year. The research sample was determined using multistage random sampling. Phase E3 served as the experimental class using the TPACK based on Project Based Learning model, while phase E8 was the control class using the conventional lecture method. Data collection techniques included modified tests on learning outcomes and creative thinking skills, consisting of three essay questions. Data were analyzed using an independent sample t-test for hypotheses 1 and 2 and MANOVA for hypothesis 3. The results of this study indicated that: 1) TPACK based on Project Based Learning significantly influenced biology learning outcomes, 2) TPACK based on Project Based Learning significantly influenced students’ creative thinking skills, 3) TPACK based on Project Based Learning significantly influenced both biology learning outcomes and students’ creative thinking skills.